Effect of vestibular rehabilitation treatment (VRT) on patients with unsteadiness after intratympanic gentamicin in Menière’s disease: protocol for a randomised controlled trial - Peixia Wu; Yue Zhou; Qiling Tong; Huiqian Yu (BMJ Open)
Introduction Menière’s disease (MD) is a multifactorial disease characterised by recurring vertigo, tinnitus and fluctuating sensorineural hearing loss as typical clinical symptoms. For patients with MD with poor response to non-invasive treatments, it is recommended to use intratympanic gentamicin treatment. The destruction of vestibular organs by gentamicin may cause residual vestibular symptoms, notably unsteadiness. However, most previous clinical studies paid little attention to this issue. Currently, vestibular rehabilitation treatment (VRT) has been proven to be an effective method for controlling vestibular symptoms and has been applied to patients with various vestibular diseases. The aim of this study is to investigate the efficacy of VRT versus usual care in MD patients who experience persistent unsteadiness for 1 month after intratympanic gentamicin treatment, in order to understand whether VRT has a positive impact on balance maintenance and vertigo control in patients with MD.Methods and analysis Randomised, assessor-blinded, controlled clinical trials will be used to compare the efficacy of balance function before and after VRT. Patients with MD who experience chronic unsteadiness for 1 month after intratympanic gentamicin treatment will be recruited and receive VRT, mainly including gaze stability training, gait rehabilitation, vestibular habituation training, etc. The outcomes assessments will be conducted at baseline and at eighth week and sixth month post-randomisation. The primary outcome will be the improvements in vestibular function quantified through the Functional Gait Assessment. The secondary outcomes will include sensory organisation test, vestibular laboratory tests (video head impulse test, caloric test and vestibular evoked myogenic potentials), Menière’s disease outcomes questionnaire, visual vertigo analogue scale and vestibular activities and participation measure.Ethics and dissemination This trial received ethical approval from the Institutional Review Board of Eye and ENT Hospital of Fudan University (reference number 2024020). The study results will be disseminated via peer-reviewed journals and conferences.Trial registration number NCT06143462.